Management of Diabetes Type-2 in our Population with Nutrition & Dietetics A Cross-Sectional Clinical Study - Muhammad Nauman Shahid, Maria Munir, Hassan Raza, Ariba Waheed, Hafsa Ashraf, Usama Javed, Naveed Shuja, (Pakistan Journal of Medical & Health Sciences, 2023)
Statistical analysis: Raw data was analyzed bio-statistically through the SPSS version 2020. Practical Implications: Current research is so informative for diabetic type-2 patients they can control their glucose levels with lifestyle medicine. Conclusion: The findings of this study suggest that a nutrition and dietetics approach can be an effective strategy for the management of type-2 diabetes in the population. It is recommended that registered dietitians work closely with patients with type-2 diabetes to develop individualized dietary plans and lifestyle modifications to improve glycemic control and other clinical outcomes. Keywords: Nutrition, Dietetics Mellitus, type-2 diabetes, Clinical outcomes, Intervention.